Nonadherence with inhaled preventer therapy in severe asthmatic patients on long-term omalizumab. Issue 2 (16th August 2018) - Allen, David J.; Holmes, Leanne-Jo; Hince, Kerry A.; Daly, Rachael; Ustabashi, Calra; Tavernier, Gael
We read with interest the paper by Lee et al. [1], reporting on the high rate of nonadherence in a group of severe asthma patients who were potentially suitable for biological therapy or bronchial thermoplasty. In our experience the issue of nonadherence is not confined to patients under active consideration for biological therapy. We have identified significant rates of nonadherence in a group of patients on long-term Omalizumab therapy. Nonadherence with inhaled preventer therapy is prevalent in previously adherent patients on long-term omalizumab http://ow.ly/5wdE30kp0MM